Issue Information. Issue 7 (28th July 2022) - Unknown
Abstract : Cover : In the last few years, numerous protein structures have been determined using cryo‐electron microscopy (cryo‐EM), and have then been deposited in the Electron Microscopy Data Bank (EMDB). To facilitate interpretation of the cryo‐EM maps, several methods have been developed that allow modelling the tertiary structure of these proteins. In this issue, Alnabati et al . describe how to use two of these methods, VESPER and MAINMAST. The cover image shows a model of the entire structure of PDB entry 4CI0, generated using VEPSER and MAINMAST. The refined full‐atom model of chain A of F420‐reducing [NiFe] hydrogenase Frh, generated from sequence using MAINMAST, is shown in blue, and the best fitted structures of chains B and C, from VESPER, are shown in green and magenta, respectively. The image of the structures was produced using UCSF Chimera (https://www.cgl.ucsf.edu/chimera/ ). Cover image provided by the authors.